Flow‐induced shear stress and deformation of a core–shell‐structured microcapsule in a microchannel. Issue 20 (14th July 2022) - Hou, Tuo; Ren, Yong; Chan, Yue; Wang, Jing; Yan, Yuying
Abstract: A numerical model was developed and validated to investigate the fluid–structure interactions between fully developed pipe flow and core–shell‐structured microcapsule in a microchannel. Different flow rates and microcapsule shell thicknesses were considered. A sixth‐order rotational symmetric distribution of von Mises stress over the microcapsule shell can be observed on the microcapsule with a thinner shell configuration, especially at higher flow rate conditions. It is also observed that when being carried along in a fully developed pipe flow, the microcapsule with a thinner shell tends to accumulate stress at a higher rate compared to that with a thicker shell. In general, for the same microcapsule configuration, higher flow velocity would induce a higher stress level over the microcapsule shell. The deformation gradient was used to capture the microcapsule's deformation in the present study. The effect of Young's modulus on the microcapsule shell on the microcapsule deformation was investigated as well. Our findings will shed light on the understanding of the stability of core–shell‐structured microcapsule when subjected to flow‐induced shear stress in a microfluidic system, enabling a more exquisite control over the breakup dynamics of drug‐loaded microcapsule for biomedical applications.